Pulmonary function and airway inflammation among dairy parlor workers after exposure to inhalable aerosols. Issue 3 (March 2017) - Nonnenmann, Matthew W.; Gimeno Ruiz de Porras, David; Levin, Jeffrey; Douphrate, David; Boggaram, Vijay; Schaffer, Joshua; Gallagher, Michael; Hornick, Madeleine; Reynolds, Stephen
Abstract : Background: Inhalation exposure to organic dust causes lung inflammation among agricultural workers. Due to changes in production and work organization, task‐based inhalation exposure data, including novel lung inflammation biomarkers, will inform exposure recommendations for dairy farm workers. Methods: Linear regression was used to estimate the associations of airborne exposure to dust concentration, endotoxin, and muramic acid with pulmonary outcomes (i.e., FEV1, exhaled nitric oxide). Logistic regression was used to estimate associations with self‐reported pulmonary symptoms. Results: Mean exposure concentration to inhalable dust, endotoxin, and muramic acid were 0.55 mg/m 3, 118 EU/m 3, and 3.6 mg/m 3, respectively. We found cross‐shift differences for exhaled nitric oxide ( P = 0.005) and self‐reported pulmonary symptoms ( P = 0.008) but no association of exposure with respiratory outcomes. Conclusions: Inhalation exposures during parlor tasks, which were lower than previously reported and were not associated with cross‐shift measures of pulmonary health among dairy workers. Modern milking parlor designs may be contributing to lower inhalation exposure. Am. J. Ind. Med. 60:255–263, 2017. © 2017 Wiley Periodicals, Inc.